Identifikasi Faktor yang Berpengaruh terhadap Penentuan Pemenang Lelang Jasa Konstruksi: (Studi Kasus Proyek Konstruksi Pemerintah Kabupaten Buton) - Nurhayati Nurhayati; Irzal Agus (Universitas Kristen Maranatha, 2023)
The implementation of construction projects involves many parties in terms of interaction and coordination. In order for the owner's wishes to be realized, the owner will choose a qualified contractor to carry out the construction through an auction process. There are several factors that influence to be able to win an auction. This study aims to determine the factors that influence the winning bidder for construction services in the Buton Regency government project which covers three (3) projects at the Public Works & Spatial Planning Office, the Education Office and the Transportation Office. The object of research from the three offices is a building project. Questionnaires were given to the contractors and then the data were analyzed using SPSS, namely regression analysis, model test, F test, T test and autocorrelation. From the results of the analysis obtained three (3) dominant factors that influence the winner of the construction service auction, namely the sub-work (X2), the good relationship between the owner and the contractor (X26) and the communication system in the project (X35).